PENGEMBANGAN BAHAN AJAR AKUNTANSI BERBASIS KOMPUTER PADA MATERI BUKU BESAR PADA MATA PELAJARAN AKUNTANSI KELAS X DI SMK YAPIM SIAK HULU: Developing of Computer-Based Accounting Teaching Materials in the Ledger Teaching Materials on Class X Accounting Lessons in Yapim Siak Hulu Vocational School of Academic Year 2016/2017 - Akhmad Suyono (Perspektif Pendidikan dan Keguruan, 2018)
The objectives of this research are: (1) to find out the process of developing accounting teaching media in the form of interactive CDs with Lectora Inspire Portable® accounting subjects in general ledger material. (2) To find out the feasibility of accounting instructional media in the form of interactive CDs with the Lectora Inspire Portable® accounting software in general ledger material. This type of research is research and development. The development model used is the Borg & Gall model which starts from the potential and problem stages to strengthen the potential and problems to be studied, the second stage is collecting information by observing school, the third stage is product design that is done in determining SK & KD, indicator, determine teaching materials and will produce a flowchart and storry board, Lectora Inspire Portable®, the fourth stage is design validation from Material Experts and Learning Practitioners with 82% and 96% revision in Phase I, and Media Experts generate 92% and 96% in the revision phase I, and continued with a small-scale trial conducted with 7 students, and continued to a large-scale trial conducted on 15 students who had different abilities, and continued with the making of products for data analysis and obtained the final product of accounting teaching materials in the form of interactive CDs. Based on the results of data analysis and discussion, the results of this study are the availability of valid accounting instructional media through the validity stage and proven feasibility through the trial phase.